Tools from the Indian space programme for observing and forecasting extreme weather events - Retrospect and prospect (MAUSAM, 2016)
Extreme weather events (EWEs) cause hardship, economic loss and have severe socio-economic consequences. It is necessary to develop forecast capability for such events so as to minimise losses and take appropriate measures for combating. Methods relying on only ground based weather observation networks are not adequate. Observations from space platforms offer regular and frequent measurements over a wide area. Observations from geostationary platforms provide information on atmospheric parameters and processes, while low earth orbiting platforms provide global observations at higher spatial resolutions. This paper describes the evolution of space programme in India, consisting of the space segment, data processing and products, and science and applications for observing and monitoring weather systems. Emphasis is on developing end-to-end capacity in weather monitoring. Forecasting of EWEs is illustrated with a few case studies. With the integration of space technology inputs, it is expected that forecast skill and lead time of the forecast will improve. Some of the future Indian space missions planned to enhance the capacity are also described. A multidisciplinary approach comprising the use of space technology, ground based measurement network and high speed computing power, can form a backbone for observing and forecasting EWEs.